Topography characteristics and formation mechanism of the bolt-hole contact interface during the bolt installation of interference-fit composite structure. (October 2022) - Yang, Yu; Zheng, Wei; Liang, Biao; Luo, Bin; Hu, Wenlong; Zhang, Kaifu; Cheng, Hui
Abstract: During the bolt installation process of interference-fit composite structure, the bolt will come to contact with the composite, forming the contact interface. Understanding the topography characteristics and formation mechanism of the contact interface is of great significance to ensure the load-bearing function of the structure. In this paper, bolt installation experiments were conducted with considering the interference-fit length and interference-fit size. The micro topography characteristics of the flat contact surface and bolt-hole contact surface were analyzed. The main topography characteristics of the flat contact surface is fiber bending and delamination, while the main topography characteristics of the bolt-hole contact surface is material shedding. Based on the topography of the bolt-hole contact interface, formation mechanism of the bolt-hole contact interface is revealed. Energy spectra results show coatings has crucial effect on the formation of bolt-hole contact interface. The main components of the bolt-hole contact interface are coating debris and composite debris, with little bolt debris. The thickness of the bolt-hole contact interface is positive related to the friction length and interference-fit size. This paper provides potential application for the determination of leakage channel and corrosion position of interference-fit composite bolted structure. Highlights: Bolt installation experiments were conducted with considering interference-fit length and interference-fit size. Topography characteristics of the contact surface were investigated. Role of coatings during the bolt installation process was analyzed. Forming mechanism of the bolt-hole contact interface was revealed.